POLITICAL WILL PEMERINTAH KOTA DUMAI DALAM PENGADAAN AIR BERSIH TAHUN 2018-2019 - Siti Nazurah; Adlin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
Clean water is one of the most important and very sensitive basic needs in human life, as well as being a basic need for the community. The need and use of clean water from year to year is increasing in line with the development of population and housing, this is directly proportional to the population growth of Dumai City which continues to increase, making the need for clean water increasing day by day. This causes the Dumai City community's rights to be unfulfilled for clean water services provided by the government. Therefore, it is very necessary to have a will or Political Will of the Dumai City Government in the provision of clean water. The purpose of this study was to determine the Political Will of the Dumai City Government in Procurement of Clean Water in 2018-2019. This study uses a qualitative descriptive method with data collection techniques are interviews and documentation.The results of the study explain that the Political Will of the Dumai City Government in the Procurement of Clean Water in 2018-2019 is not yet optimal. This is because first, the Dumai City Government's initiative in the provision of clean water is considered only limited to planning and formulation. Second, the clean water supply program always experiences delays from the planned timeline and the amount of water distributed does not meet the needs of the people of Dumai City. Third, the Dumai City Government does not involve the community in the clean water supply process. Fourth, the Dumai City Government has not been able to maximize the existing budget properly. Fifth, the sustainability of the Dumai City Government's efforts in the provision of clean water is considered to be lacking. Sixth, the Dumai City Government still has not implemented lessons from areas with better clean water conditions.Keywords: Political Will and Clean Water Supply